Role of Eco-Friendly Products in the Revival of Developing Countries’ Economies and Achieving a Sustainable Green Economy - Mustafa, Sohaib; Hao, Tengyue; Jamil, Khalid; Qiao, Yu; Nawaz, Muhammad (Frontiers in Environmental Science, 2022)
A sustainable green economy is the need of time, and eco-friendly products can play a decisive role in this goal. Low consumption of eco-friendly products is a serious concern of researchers and policymakers. To address this issue, we have studied the phenomenon in a developing country and provided insights to researchers and policymakers about the factors that influence the consumers' behaviour in developing behaviour. We have designed an integrated model based on UTAUT to study the developing countries' behavioural intentions towards eco-friendly products. 805 useable sample is obtained to analyze by implying SEM-ANN dual-stage hybrid model. Results revealed that environmental knowledge is a significant predictor and a moderator, but consumers are less educated about ecological issues in developing countries. Results also revealed that male and female consumers' preferences are differently influenced by factors studied to measure adoption intentions of eco-friendly products. Sensitivity analysis results revealed that social influence followed by effort expectance and perceived expectancy of eco-friendly products are more important for developing countries' customers. The study also provides empirical evidence of methodological advancement using SEM-ANN and suggests implying a dual-stage hybrid model in studies where human behaviour is involved.